Medicolegal Examination of Sexual Assault Survivors (Medical Forum Monthly, 2021)
Objective: To identify the reasons of discrimination in medico-legal assessment and reports of sexual assault survivor.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Study Department of Forensic Medicine, Nishtar Medical College (NMU) Multan, Pakistan during January 2020 to March 2020.Materials and Methods: Record of 133 cases of sexual assault reported during a period of two years from January 2017 to January 2019 to the medico-legal section of Forensic Medicine Department of Nishtar Medical University, Multan were examined in detail and transferred to a designed Performa. Statistical analysis was done using SPSS version 20. Results: Of the total 133 cases, 73.6% were examined more than 72 hours after the incidence while only 4.5% examined in first 24 hours. Majority (64.6%) belonging to the age of 11-20 years were reported to be victimized in this heinous crime. Most common type of injury was tear / laceration involving (80.4%) cases including both fresh (18%) and healed (62.4%). Abrasion and bruising of labia minora in 13(9.7%) and bruise of vagina was present in 7(5.2%) of the total cases. Medical reports and laboratory findings were consistent in (43.6%) cases whereas; 73(54.8%) cases showed discrepancy between the medical reports and laboratory data.Conclusion: Sexual assault is more common in younger females. Late presentation for examination is one of the root causes of discrepancy between medico-legal assessment and reports of Forensic Science Laboratory. There is need to educate the young people regarding sexual assault and training of forensic examiners to evaluate such cases properly with meticulous collection of evidence so that justice can prevail.Objective: To identify the reasons of discrimination in medico-legal assessment and reports of sexual assault survivor.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Study Department of Forensic Medicine, Nishtar Medical College (NMU) Multan, Pakistan during January 2020 to March 2020.Materials and Methods: Record of 133 cases of sexual assault reported during a period of two years from January 2017 to January 2019 to the medico-legal section of Forensic Medicine Department of Nishtar Medical University, Multan were examined in detail and transferred to a designed Performa. Statistical analysis was done using SPSS version 20. Results: Of the total 133 cases, 73.6% were examined more than 72 hours after the incidence while only 4.5% examined in first 24 hours. Majority (64.6%) belonging to the age of 11-20 years were reported to be victimized in this heinous crime. Most common type of injury was tear / laceration involving (80.4%) cases including both fresh (18%) and healed (62.4%). Abrasion and bruising of labia minora in 13(9.7%) and bruise of vagina was present in 7(5.2%) of the total cases. Medical reports and laboratory findings were consistent in (43.6%) cases whereas; 73(54.8%) cases showed discrepancy between the medical reports and laboratory data.Conclusion: Sexual assault is more common in younger females. Late presentation for examination is one of the root causes of discrepancy between medico-legal assessment and reports of Forensic Science Laboratory. There is need to educate the young people regarding sexual assault and training of forensic examiners to evaluate such cases properly with meticulous collection of evidence so that justice can prevail.